Analisis Implementasi Pendampingan Keuangan Dan Strategi Digital Marketing Terhadap Pengembangan Usaha Mustalik Dalam Program EMAS LMI - Syalaisa Amani Fatihah; R. Yuniardi Rusdianto (Jurnal Riset dan Inovasi Manajemen, 2024)
The Community Economic Program (EMAS) has an important role in the community, especially to provide support to community groups and individuals who have potential with the aim of increasing income with various efforts, namely providing access to business capital, training, and guidance needed to advance the business. With the current era shifting to digitalization, it is necessary to implement it as a form of mustahik business development. The purpose of the study is to analyze the implementation of the results and impact of business development assistance in the form of financial report assistance and digital marketing on the Community Economy program. This study used field research methods by collecting data through direct observation and focus group discussions. The collected data was analyzed descriptively to identify the success of the implementation of the interventions that have been given to the Community Economic Program (EMAS) KSM Malang. The results showed that this EMAS program can have a positive impact on the development and increase of mustahik business in increasing the number of consumers after being provided with financial report assistance and introducing digital marketing to LMI assisted mustahik.